Catalan currency as an opportunity and symbol of self-governance: From the War of the Reapers to the Civil War - Albert Estrada-Rius (Catalan Historical Review)
This article provides a brief overview of the role of Catalonia’s own currency from the War of the Reapers to the Spanish Civil War in an effort to point out how the exceptionalism of the conflicts spurred the development of Catalonia’s own currency, with the need for such currency coupled with the opportunity of symbolic vindication offered by currencies, one of the most prized symbols of identity and self-governance.